Sex differences and the effect of female sex hormones on auditory function: a systematic review - Aloufi, Nada; Heinrich, Antje; Marshall, Kay; Kluk, Karolina (Frontiers in Human Neuroscience, 2023)
Aims: To discuss sex differences in auditory function between women and men, and whether cyclic fluctuations in levels of female sex hormones affect auditory function in premenopausal and postmenopausal women. To systematically review the literature concerning the discussed patterns in order to give an overview of the methodologies used in research. To identify the gap in knowledge and to make recommendations for future work. Methods: PECOS criteria were used in developing the review questions. The review protocol follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and was pre-registered in the Prospective Register of Systematic Reviews. EMBASE, PubMed, MEDLINE, PsycINFO, ComDisDome, CINAHL, Web of Science, Cochrane Central Register of Controlled Trials via Cochrane Library, and scanning reference lists of relevant studies, and internet resources were used. The quality of evidence was assessed using the Newcastle-Ottawa Scale. Result: Women had more sensitive hearing (measured at the level of peripheral and central auditory system) than men. Auditory function in women fluctuated during the menstrual cycle, while no such fluctuations in men over the same time period were reported. Hearing sensitivity improved in women during the late follicular phase, and decrease during the luteal phase, implying an effect of female sex hormones, although the specific effects of estradiol and progesterone fluctuations on the central auditory system remain unclear. Hearing sensitivity in women declined rapidly at the onset of menopause. Conclusion: Consistent sex differences exist in auditory function across the auditory pathway with premenopausal women often showing better function than men. Premenopausal women show fluctuations in hearing function across the menstrual cycle with a better function during the peak of estradiol or when the ratio of estradiol to progesterone is high. Menopause marks the onset of hearing loss in women, characterised by a rapid decline in hearing sensitivity and a more pronounced loss than in men. The systematic review highlights the need for well-designed and -controlled studies to evaluate the influence of estradiol and progesterone on hearing by consistently including control groups, using objective tests to measure hormonal levels, and by testing participants at different points across the menstrual cycle.